Propagation Measurements during Daytime for RazakSAT S-Band Space to Earth Satellite Signal Transmission - Atikah Balqis, Basri; Khairayu, Badron; Ahmad Fadzil, Ismail; Abadi, Chanik; Hamid, Salim; Maszlan, Ismail (Science & Engineering Research Support Society (SERSC), 2018)
Adequate fade margins for all conditions are critical in ensuring reliable satellite operation. The required fade margin value for specific desired quality of service (QoS) can be established from the statistics of outage due to attenuation. In the case of clear sky attenuation, the value is much dependent on the atmospheric layer conditions and their compositions. For absolute Free Space, the signal loss is only dependent on distance and frequency. In this study, the effects of distance were analysed in the investigation of identifying the most appropriate clear sky attenuation values during daytime. The RazakSAT received signal levels were matched according to the distances between the satellite and the Ground station. Clear sky conditions were confirmed using S-band (Terminal Doppler Weather Radar) TDWR reflectivity information. With this value, the satellite operator can decide execution of power uplink and mitigation technique if necessary. The RazakSAT S-band (2.232 GHz) transmission signal data of were furnished by Malaysian National Space Agency (ANGKASA) and radar data were acquired from Malaysian Meteorology department (MMD). The findings offer awareness of required fade margin as distance varies during each flight path. The collected data will also be employed in the investigation of Free Space Path Loss (FSPL) formulation applicable for satellite link in tropical region.